Ethical Dilemma of Earnings Management: Solution or Problem? - Rizki Meidira Adhyaksa (Cerdika: Jurnal Ilmiah Indonesia, 2024)
This study explores the ethical dilemmas surrounding earnings management, assessing whether earnings management serves as a beneficial strategy or a detrimental practice in the long run. The authors use qualitative methods to analyze literature that highlights both positive and negative aspects. The results show that earnings management can increase firm value in the short term but is contrary to ethical standards. This study emphasizes the importance of professional ethics as a guiding framework for accountants when facing pressure to engage in earnings management. The authors conclude that although earnings management may offer short-term benefits, its negative ethical implications and potential long-term risks outweigh the benefits.